IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA DALAM IKHTIAR MENUMBUHKAN AQIDAH AKHLAK ANAK USIA DINI - Munawir; Sholikha, Risma Amaliatu; Romadhona, Alifya Sa'diyah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
Learning was essentially a planned effort by teachers consciously in order to help students to meet their needs for education can also form fundamental skills and help someone to be proficient in carrying out life tasks so that the learning process occurs in him. There was an educative interaction between the teacher as a teaching subject and students as a learning subject so that an effective learning process occurs. The goals of national education will be achieved if there was appropriate and responsible cooperation between the three parties. The basic character of a person was actually formed in childhood and continues throughout life. This shows the importance of character education as an important part of basic education. The method used in this study was qualitative method. In this study, literature research methods were used, where library materials were used as data sources for the formulation of research problems. Based on the results of the analysis, morals can also be influenced by good and bad education. If a person maintains these conditions, chooses virtue and righteousness, loves the good, is passionate about the good, habituates himself to love the beautiful and hates the ugly, all this will become his character.